No Evidence for Cognitive Dysfunction or Depression in Patients with Mild Restless Legs Syndrome - Driver-Dunckley, Erika (2009)
Restless legs syndrome is a common disoder that may interrupt sleep and has been reported to produce daytime fatigue and/or mood changes. This study assessed whether patients with RLS have more cognitive dysfunction and depression than individuals of the same age and education who do not have RLS. The study showed that older individuals with mild RLS for at least 1 year do not have cognitive dysfunction and are not depressed compared with a control group of similar age and education.